The Relation between Spatial Organization of the City and Its Function - Wahda Shuker Al-Hinkawi (Iraqi Journal of Architecture and Planning, 2009)
The city , is one of the expanded and most complex systems that the human beingsever known, as it exist through continuous development and changing process throughtime. Each generation extends , substitutes , re-arranges and adopts what it inheritsbefore passing with to the new generation, therefore the city can be called in amoment of time as a group of dynamic processes more than being constant facts. Thecity is a product of a large number of resolutions within its reality, having the smalland large measurement to be connected with the social structures and ideologicalconstructions of its occupant, that community creates over time, but remains obscureto the individuals at any moment.The obvious similarity of the cities urban structures overtime and in differentparts of the world, indicates to the existence ofmain types ofspatial organization,beyond different structures, which refer to the possibility of building theoreticalconcepts regarding a spatial theory of the city, through gaining access to the basiclogic in creating the physical structures of the city'more over to explain the relationbetween the city form and its function .The research based on the concept of spaoe in dealing with the urban structureof the city and considered to be the essence in constructive logic, in more specificallybuilding distribution creates a continuous system of spaces that connect buildings in aspatial system that reflects the structure ofthe city, so reaching out to the languagethat expresses the spatial organization, which requires illustration of the commonspatial properties ofthe cities and their differencesThe research idea, based on these concepts, regarding the space as mightprovide a common language to the different city forms and some is the relationbetween the city structure and the method that perlorm its function withThereby, these concepts were examined in Al - Khadimya fabric, regards as acomplete physical system that testified great transformation in its physical, social andfunctional structure through time.The research, has reached out to explain the relation between the changing inthe spatial organization properties of the urban fabric and the natural growh oftheland use.